Estudio de la regulación contable para pymes en Colombia: Una mirada desde las problemáticas en el contexto latinoamericano - Patiño Jacinto, Ruth Alejandra (2023)
This paper focuses on the relevance that Small and Medium Enterprises [SMEs] have in the growth of a country, therefore the objective of the work is to analyze the accounting regulatory alternatives that countries such as Colombia, Ecuador, Peru, Argentina, Mexico, and some basic aspects of Chile, Bolivia and Brazil have assumed in the process of adoption of IFRS for SMEs; for this purpose a qualitative methodology is used, based on a documentary review and focused on accounting for the common and recurrent problems of the convergence process. As a result of the respective content analysis of the documents found, the following categories of the problems encountered are established: effects of the convergence process on the users of financial information and decision making, asymmetries in the accounting treatment in the IFRS for SMEs, costs in the generation of information, and, some demographic and particular aspects. Finally, the alternatives of accounting regulation for SMEs that have been developed in some Latin American countries are collected, finding that some countries have adopted IFRS for SMEs, such as Colombia, others allow IFRS for SMEs on a voluntary basis, such as Argentina; Mexico has local standards and Brazil opted for convergence.